Molecularly Tailored Interface for Long‐Term Xenogeneic Cell Transplantation. (7th October 2021) - Madhurakkat Perikamana, Sajeesh Kumar; Seale, Nailah; Hoque, Jiaul; Ryu, Ji Hyun; Kumar, Vardhman; Shih, Yuru Vernon; Varghese, Shyni
Abstract: Encapsulation of therapeutic cells in a semipermeable device can mitigate the need for systemic immune suppression following cell transplantation by providing local immunoprotection while being permeable to nutrients, oxygen, and different cell‐secreted biomolecules. However, fibrotic tissue deposition around the device has been shown to compromise the long‐term function of the transplanted cells. Herein, a macroencapsulation device design that improves long‐term survival and function of the transplanted cells is reported. The device is comprised of a semipermeable chitosan pouch with a tunable reservoir and molecularly engineered interface. The chitosan pouch interface decorated with 1, 12‐dodecanedioic acid (DDA), limits the cell adhesion and vigorous foreign body response while maintaining the barrier properties amenable to cell encapsulation. The device provides long‐term protection to the encapsulated human primary hepatocytes in the subcutaneous space of immunocompetent mice. The device supports the encapsulated cells for up to 6 months as evident from cell viability and presence of human specific albumin in circulation. Solutions that integrate biomaterials and interfacial engineering such as the one described here may advance development of easy‐to manufacture and retrievable devices for the transplantation of therapeutic cells in the absence of immunosuppression. Abstract : A macroencapsulation device for xenogeneic cell transplantation is developed. The device consists of a porous chitosan pouch with an adhesive inner surface that promotes cell viability and a cell repellent outer surface that minimizes fibrosis. The device supports long term (6 months) transplantation of human primary hepatocytes into an immunocompetent mice.